2000
DOI: 10.1002/1096-9861(20000108)429:2<253::aid-cne6>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Confocal microscopic study of glial-vascular relationships in the retinas of pigmented rats

Abstract: Astroglia are interposed between the cerebral vasculature and neurons, where they may mediate the transfer of substances from the circulation to neurons and couple changes in neuronal activity to changes in cerebral blood flow. The retina is a particularly advantageous model system for studying glial-vascular interactions in situ. Confocal microscopy and three-dimensional image reconstruction were used to study the anatomical relationships between glia and the surface vasculature in retinas acutely isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 75 publications
1
21
0
Order By: Relevance
“…In addition, we have shown that only perivascular astroglia express the transporter, indicating a specialized function for the different astrocytes within the nerve fiber layer. Perivascular astroglia are intricately related to the development of inner retinal vessels (57) and have recently been linked to regulation of communication within the nerve fiber layer (48). Our identification of the CRT in the retinal pigmented epithelium indicates that creatine can also be obtained from the choroidal circulation.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In addition, we have shown that only perivascular astroglia express the transporter, indicating a specialized function for the different astrocytes within the nerve fiber layer. Perivascular astroglia are intricately related to the development of inner retinal vessels (57) and have recently been linked to regulation of communication within the nerve fiber layer (48). Our identification of the CRT in the retinal pigmented epithelium indicates that creatine can also be obtained from the choroidal circulation.…”
Section: Discussionmentioning
confidence: 79%
“…To determine whether astrocytes of the nerve fiber layer expressed CRT, we labeled the retina with GFAP. In a vertical section of the rat retina, it is difficult to show the symmetrical stellate form of GFAP-positive astrocytes encountered outside the optic nerve area (41,57). However, GFAP labeling of the short radiating processes of astrocytes (Fig.…”
Section: Specificity Of Crt Antibodies By Western Blotting Of Membranmentioning
confidence: 99%
“…In the retina, astrocytes are found exclusively in the nerve fibre layer. Zahs and Wu (2001) demonstrated morphologically that there are at least two subclasses of astrocyte within the retina: intervascular astrocytes, which are located between the major arterioles, and vascular astrocytes, which have an Fig. 4 Immunofluorescent labelling of EAAT4 (A) and GLAST (B) and areas that colocalize (C).…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes are confined to those retinae that have an inner retinal blood supply and have an intricate relationship with retinal blood vessels (Zahs and Wu 2001). They are thought to be important for development of the retinal vasculature and maintaining the blood retinal barrier.…”
Section: Discussionmentioning
confidence: 99%
“…They are actively involved in uptake and degradation of the amino acid neurotransmitters, glutamate and GABA, are involved in shuttling energy metabolites to neurons and are also important for maintenance of the blood-retinal barrier [9][10][11]. Astrocytes are intricately linked with the vasculature and have processes within the nerve fibre and ganglion cell layers [12]. The function of astrocytes within the retina is not clearly defined, although they do express glutamate transporters such as GLAST and EAAT4 [13,14].…”
Section: Introductionmentioning
confidence: 99%